Biquadratic exchange in the diluted Ising ferromagnet - Tiwari M.; Chaturvedi N.; Shrivastava R.N. (My University, 2025)
Effects of biquadratic exchange on Curie temperature and specific heat have been studied in the light of a new effective field theory for the Ising Spin System. The nearest neighbour interaction is taken into account. © 1987.